Impact of Human Capital on Poverty Reduction in Pakistan - Rashid, Rashid Naweed; Saeed, Muhammad Kashif; Ali, Hashim (iRASD Journal of Economics, 2022)
This paper determines the impact of various health indicators on poverty reduction in Pakistan. Health indicators affect the Poverty through increasing Labor productivity and through improving Education. GNP per capita is a proxy variable for poverty reduction. Life Expectancy, infant mortality rate, total health Expenditures, and Population per doctor are explanatory variables in Model 1. The study has regressed these health indicators on Education in Model 2. To determine the Short-run and long run relationship among the variables the research applied the Co-integration (ARDL) and Error Correction Model. The study uses the Augmented- Dickey-Fuller test to check the unit root. The study has analyzed the time series data of Pakistan from 1985 to 2021.The research finds that health indicators like: Life expectancy and Infant mortality increase the GDP per Capita in the long run. The health indicators also have positive effects on education and as a result, Education increases the GDP per capita in the short- run and long run. The research concludes that improvement in human capital leads to decrease the poverty and to improve the health and education sectors of the society. The major policy implication of this study is that to decrease poverty and look for a healthy and educated society, then the government should urgently and seriously focus on the health sector of Pakistan.